Android Application Prototype of Basic BISINDO Introduction and Practice for General People - Fadlilah, Umi; Mahamad, Abd Kadir; Handaga, Bana; Saon, Sharifah; Ratih, Koesoemo; Rahmawati, Laili Etika; Thamrin, Husni (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
One of the sign languages used in Indonesia is BISINDO (Indonesian Sign Language) created by the deaf. BISINDO is like the mother tongue for the deaf in Indonesia, although it is not as popular as SIBI (Indonesian Sign System). Therefore, the researchers propose to develop an Android-based prototype to promote BISINDO to others and help the deaf in daily communication. This prototype was built using coding in React Native framework and code editor of Visual Studio Code, then it was compiled to an Android Smartphone. The features include BISINDO's basic dictionary, translation from hand gesture to text, voice to sign language, text to sign language, and voice to text. This prototype is expected to introduce basic BISINDO vocabulary and practice using BISINDO. This prototype ia expected to be developed further into a more useful application, especially to assist communication between deaf people and the general public, but not as a substitution of BISINDO teachers.